The Influence of Work Discipline, Employee Engagement, and Work Culture on Employee Performance at the Buleleng District Office - Budiarsana, Kadek; Trianasari, Trianasari; Widiastini, Ni Made Ary (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study aims to determine the influence of work discipline, employee engagement, and work culture on employee performance. This research employs a quantitative approach using a survey method. The population in this study consists of all employees, with the sampling technique using a saturated sampling method. Data were collected through the distribution of questionnaires using a Likert scale. The data analysis technique used in this study is multiple linear regression analysis with the assistance of SPSS software. The results show that partially, work discipline has a positive and significant effect on employee performance. Employee engagement also has a positive and significant effect on employee performance. In addition, work culture has a positive and significant effect on employee performance. Simultaneously, work discipline, employee engagement, and work culture influence employee performance. The research model indicates that the independent variables are able to explain employee performance, although there are other factors outside the research model that also influence it.